A RAPGEF6 variant constitutes a major risk factor for laryngeal paralysis in dogs - Hadji Rasouliha, Sheida (2019)
Laryngeal paralysis (LP) is the inability to abduct the arytenoid cartilages during inspiration, resulting in a partial to complete airway obstruction and consequent respiratory distress. Different forms of LP with varying age of onset exist in dogs. Hereditary early onset forms were reported in several dog breeds. In most breeds, hereditary LP is associated with other neurologic pathologies. Using a genome-wide association study and haplotype analyses, we mapped a major genetic risk factor for an early onset LP in Miniature Bull Terriers to a ~1.3 Mb interval on chromosome 11. Whole genome sequencing of an affected Miniature Bull Terrier and comparison to 598 control genomes revealed a 36 bp insertion into exon 15 of the RAPGEF6 gene (c.1793_1794ins36). The imperfect genotype-phenotype correlation suggested a complex mode of inheritance with a major genetic risk factor involving a recessive risk allele. Homozygosity for the insertion was associated with a 10- to 17-fold increased risk for LP. The insertion allele was only found in Miniature Bull Terriers and Bull Terriers. It was absent from >1000 control dogs of other dog breeds. The insertion sequence contains a splice acceptor motif leading to aberrant splicing in transcripts originating from the mutant allele (r.1732_1780del). This leads to a frameshift and a premature stop codon, p.(Ile587ProfsTer5), removing 64% of the open reading frame. Our results suggest an important role of RAPGEF6 in laryngeal nerve function and provide new clues to its physiological significance.